IMPROVING THE PEDAGOGICAL CONDITIONS FOR THE INTRODUCTION OF COPYRIGHT TECHNOLOGIES (ON THE EXAMPLE OF THE SUBJECT OF PEDAGOGY) - Alimdjanova Dilbar Negmatovna (Scholar Express Journal, 2021)
New priorities in education encourage teachers to search for new modern effective teaching technologies that allow them to achieve higher learning and upbringing results, to introduce new educational technologies into the educational process, namely, personality-oriented pedagogical technologies.
Keywords: Knowledge; effectiveness of learning; creative abilities; human resources.